2018
DOI: 10.1038/s41467-018-03271-3
|View full text |Cite
|
Sign up to set email alerts
|

CryoEM structure of the human SLC4A4 sodium-coupled acid-base transporter NBCe1

Abstract: Na+-coupled acid–base transporters play essential roles in human biology. Their dysfunction has been linked to cancer, heart, and brain disease. High-resolution structures of mammalian Na+-coupled acid–base transporters are not available. The sodium-bicarbonate cotransporter NBCe1 functions in multiple organs and its mutations cause blindness, abnormal growth and blood chemistry, migraines, and impaired cognitive function. Here, we have determined the structure of the membrane domain dimer of human NBCe1 at 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
129
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(137 citation statements)
references
References 71 publications
4
129
2
2
Order By: Relevance
“…The model of the SLC26Dg dimer displays a protomer-protomer membrane interface that is remarkably different from the membrane interfaces observed for the SLC4 and SLC23 families, both in its location and in its size 17,18,19,21,22 . Whereas the membrane dimer interfaces of SLC4 and SLC23 proteins center around TM6, and TM5 plus TM12, respectively, the midpoint of the SLC26Dg dimer is TM14 on the opposite side of the gate domain.…”
Section: Structural Model Of the Slc26dg Membrane Dimer Interfacecontrasting
confidence: 58%
See 3 more Smart Citations
“…The model of the SLC26Dg dimer displays a protomer-protomer membrane interface that is remarkably different from the membrane interfaces observed for the SLC4 and SLC23 families, both in its location and in its size 17,18,19,21,22 . Whereas the membrane dimer interfaces of SLC4 and SLC23 proteins center around TM6, and TM5 plus TM12, respectively, the midpoint of the SLC26Dg dimer is TM14 on the opposite side of the gate domain.…”
Section: Structural Model Of the Slc26dg Membrane Dimer Interfacecontrasting
confidence: 58%
“…Dimeric states have been previously observed for pro-and eukaryotic members of the SLC4 25,26,27 , SLC23 28 , and SLC26 4,29,30,31,32 families. Recent structures subsequently confirmed this oligomeric state for SLC4 17,18,19 and SLC23 21,22 proteins and indicated that in both families the gate domains form the main interaction surface between protomers, though each family appears to hold a distinct dimer interface. As the crystal structure of SLC26Dg captured the protein in a monomeric state, the mode of interaction between SLC26 protomers has remained elusive.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Recently, Huynh et al . (2018) determined the structure at 3.9 Å of the membrane‐domain dimer of human NBCe1 by cryo‐electron microscopy (cryo‐EM). However, they could not model the cytosolic Nt, part of extracellular loop 3 (EL3), EL4, intracellular loop 5 (IL5), and cytosolic Ct due to the dynamic nature of these regions, which nevertheless could be very important for protein regulation.…”
Section: Discussionmentioning
confidence: 99%